Knowledge, attitude and practice of community mediators in Malaysia - Ahmad, Sa’odah; Kahar, Rojanah; Hasbullah, Muslihah (Universiti Sains Malaysia, 2022)
Family and neighbourhood issues are distinctly sensitive and emotional. They might also not be suitable to be settled using the existing courtroom device in the form of adjudication. It has been acknowledged that procedures in court have failed to address the emotional state of the disputants. The alternative way to resolve the dispute is by using mediation. A study was conducted among 217 community mediators selected to determine their knowledge, attitude and practice of community mediation. A self-administered questionnaire was used to gather the research data. The results revealed that the majority of the respondents (97.7%, n = 212) know that mediation is used to resolve community disputes. All respondents agreed that mediation helps in alleviating disputes in the community. The majority of the respondents (92.2%, n = 200) agreed that mediation is an important source of information and help for the community. The majority of the respondents (99.5%, n = 216) agreed that cooperation between mediators and members of the community is very important in reducing domestic disputes and gaps in the community. The study also found that a little over half of the respondents have a low attitude (51.2%, n = 111) on community mediation. Furthermore, listening to both disputants was the most (87.1%, n = 189) practiced technique used by the respondents in dispute resolution. The study concluded that the respondents have good knowledge of community mediation, a low regard for community mediation, and practise various techniques in resolving the disputes. Most of the respondents have fewer than 10 years of experience as a community mediator. Thus, it is understandable why they do not yet have a high attitude towards community mediation.